Efficacy of Percutaneous Transluminal Angioplasty on Dysfunctional Fistulae Because of Inflow Stenosis. Issue 3 (July 2013) - Caeiro, Fernando; Carvalho, Dulce; Cruz, João; Santos, João Ribeiro; Nolasco, Fernando
Purpose: Autogenous fistulas are the preferential vascular access for hemodialysis. The aim of this retrospective study was to determine the efficacy of angioplasty for dysfunctional fistulas because of inflow dysfunction. Methods: We reviewed all the angiographic procedures performed on our institution between April 2007 and April 2009. Procedures performed in dysfunctional fistulas because of inflow stenoses were analyzed. Fistulas with stenoses out of these areas were excluded. The following data were collected: patient age and sex, fistula age at the time of intervention, location of fistula, number and location of stenosis, angiography referral criteria, clinical findings (presence or absence of thrills, bruits and pulsatility) and date of reintervention or failure. Results: During the study period 215 fistulas were submitted to angiography of which, seventy-one presented inflow stenosis (33%). Mean follow-up was 21.72±9.26 months, and average age was 7.03 months. Two groups were considered: 31 fistulas comprising ≤6 months old, and 40 fistulas >6 months old. Primary patency rates±SE for older fistulas at 6, 12, 18 and 24 months, respectively, was 91.3%± 0.04%, 80.7%± 0.07%, 53.8% ±0.10% and 34.2±0.1%. versus 91.7±0.08%, 57.1 ±0.14%, 23±0.14%, 11.4%± 0.1% for younger fistulas (P=0.04). Fistulas ≤6 months old and multiple stenosis were associated with a poorer primary patency rate (P=0.005). Conclusions: Inflow stenosis is frequently associated with fistula dysfunction. In this study we only analyzed AVF with inflow stenosis and we have shown that angioplasty can have great patency results, particularly for single lesions in matured fistulas.